OCT4 and SOX2 Specific Cytotoxic T Cells Exhibit Not Only Good Efficiency but Also Synergize PD-1 Inhibitor (Nivolumab) in Treating Breast Cancer Stem-Like Cells and Drug-Resistant Breast Cancer Mice - Peng, Wei; Chang, Liang; Li, Wenqiang; Liu, Yanan; Zhang, Min (Frontiers in Oncology, 2022)
Abstract Purpose: This study aimed to investigate the effect of OCT4&SOX2 specific cytotoxic T lymphocytes (CTLs) plus programmed cell death protein-1 (PD-1) inhibitor (nivolumab) on treating breast cancer stem-like cells (BCSCs) in vitro and drug-resistance breast cancer (DRBC) mice in vivo. Methods: In total, 160 breast cancer patients were enrolled following the immunofluorescence assay to detect tumor OCT4 and SOX2 expressions. CD154-activated B cells were co-cultured with CD8+ T cells (from breast cancer patients) in the presence of OCT4&SOX2 peptides, CMV pp65 peptides (negative control), and no peptides (normal control). MCF7-BCSCs were constructed by drug-resistance experiment and sphere-formation assay, then DRBC mice were constructed by planting MCF7-BCSCs. Subsequently, different doses of OCT4&SOX2 CTLs and PD-1 inhibitor (nivolumab) were used to treat MCF7-BCSCs and DRBC mice. Results: OCT4 and SOX2 correlated with poor differentiation, more advanced stage, and worse prognosis in breast cancer patients. In vitro, OCT4&SOX2 CTLs with effector-target ratio (ETR) 5:1, 10:1 and 20:1 presented with increased cytotoxic activity compared to CMV pp65 CTLs with ETR 20:1 (negative control) and Control CTLs with ETR 20:1 (normal control) on killing MCF7-BCSCs. Besides, PD-1 inhibitor (nivolumab) improved the cytotoxic activity of OCT4&SOX2 CTLs against MCF7-BCSCs in a dose-dependent manner. In vivo, OCT4&SOX2 CTLs plus PD-1 inhibitor (nivolumab) decreased tumor volume and tumor weight while increased tumor apoptosis rate compared to OCT4&SOX2 CTLs alone, PD-1 inhibitor (nivolumab) alone, and control. Conclusion: OCT4&SOX2 CTLs exhibit good efficiency and synergize PD-1 inhibitor (nivolumab) in treating BCSCs and DRBC.